If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + t = 49 Solving 36 + t = 49 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + t = 49 + -36 Combine like terms: 36 + -36 = 0 0 + t = 49 + -36 t = 49 + -36 Combine like terms: 49 + -36 = 13 t = 13 Simplifying t = 13
| 16a+30-5a=14a | | k+2.9=9.3 | | 3x+7=(5x+-4)*2 | | 3x+25=11x-4 | | -6x-17=-131 | | 5x^2=6x+4 | | (-9)*(-9)= | | x^3-4x^2-9X+36= | | 48+e=71 | | x(5+13)=559 | | 0.6=0.3d-12 | | o+3.7=6.2 | | x+29=41 | | -82=6+8x | | 27x=80.73 | | (5n+3n)-2=5 | | (5x-4)2=0 | | 81x^2y^2-25= | | 25x-49x=24 | | 11-10x=111-38x | | A+(x)=bc | | 4m=60 | | 3(x+5)(x+5)=21 | | 12c=8,616 | | 3(x+5)2=21 | | t^2-6t+5=0 | | 4a-12=5a+51 | | P-2L=2W | | -4+9=53 | | -4x+9=34 | | 1+1=9 | | 2.5g=17.5g |